Politik Identitas Etnis Dalam Pemilihan Kepala Daerah. Studi Kasus : Peranan Etnis Tionghoa Dalam Pilkada Kota Tebing Tinggi Tahun 2017 - Muhammad Saleh; . Yuslim; Bakaruddin Rosyidi (Jayapangus Press, 2018)
The decentralization politics that occurred in the era of reformation has encouraged the ambition of the ethnic identity politics which give a big contribution in the appearance of small kings in every region. Schmitterian explained that liberalization politics will activate the certain rights that be owned by each person individually and social groups and cover them from the cruel deeds or the third group. At the level of ethnic at least liberalization can be seen from the availability of spaces for every society to form their own community that can protect their rights, and also the decrease of the intervention of the nation in the political appreciation of every group.